Characteristics of soil physical properties in different soil management of oxisols and inceptisols - Naro Pandapotan Pasaribu; Enni Dwi Wahjunie; Suria Darma Tarigan (Universitas Trunojoyo Madura, 2023)
Oil palm (Elaeis guineensis Jacq.) is a plantation crop that has a bright future. Soil management such as land clearing, burning, use of heavy equipment and fertilisation in oil palm plantations will affect changes in soil physical properties. This study aims to assess the physical properties of soil in various treatments (planting circle, dead interplant spacings and live interplant spacings) on Oxisol and Inceptisol soil types. This research was conducted in Rancabungur and Malingping Banbten in October 2021 - May 2022. The method used in this study was multistage random sampling. Soil samples were taken from the Malingping area of Banten for the Oxisol soil type (2005 and 2009 planting years), and the Rancabungur area for the 2005 Inceptisol soil type. Comparison of soil physical properties of Oxisol of 2005 planting year with Oxisol of 2009 planting year and the ratio of Oxisol soil type of 2005 planting year and Inceptisol of 2005 planting year in various treatments did not show significant differences in soil physical properties (organic matter, content weight, field capacity moisture content, permanent wilting point, and particle density) between planting circle, dead interplant spacings and live interplant spacings. However, there were significant differences in the physical properties of soil texture between each management and permeability.